The Influence of Return On Assets (ROA), Return On Equity (ROE), and Non-Performing Loans (NPL) on Profit Growth in Banking Companies from 2021 to 2023 - Suryawan, Teguh (PT Mattawang Mediatama Solution, 2024)
Profit growth is a benchmark for evaluating a company's performance (to assess management's performance in operating the company). This study aims to analyze the relationship between profit growth and Return on Assets (ROA), Return on Equity (ROE), and Non-Performing Loan (NPL). This is an associative research study that aims to identify the relationships between variables to interpret the existing issues. The data used are secondary data in the form of financial reports from the top 10 banks from 2000-2023. The financial report data were obtained from www.idx.co.id. The collected data were then analyzed using Multiple Linear Regression analysis with the help of IBM SPSS 25.00 software. The results of this study indicate that Return on Assets (ROA) and Non-Performing Loans (NPL) do not affect profit growth, whereas Return on Equity (ROE) has a negative effect on profit growth in Indonesian banking.